Studies on goat hydroxyapatite/commercial inert glass biocomposites - OKTAR, FAİK NÜZHET; AKYURT, NURAN (SPRINGER, 2019)
In this study, mechanical properties and microstructural analysis of goat-derived hydroxyapatite/commercial inert glass biocomposites are considered in the temperature range between 1000 and 1300 degrees C. The results indicate that the best values of maximum compressive strength and microhardness are achieved in the samples sintered at 1200 degrees C for the glass in the weight of 5 and 10%. Moreover, above 1000 degrees C, decomposition of hydroxyapatite and new phase formations such as whitlockite and silicocarnotite play also a major role in the hardness and strength for goat hydroxyapatite/commercial inert glass biocomposites.
Keywords: Biomaterials; Goat-derived hydroxyapatite; Glass; Sintering; Mechanical properties; MECHANICAL-PROPERTIES; COMPOSITES; BONE; CERAMICS; APATITE